DC POWER SUPPLY SIMULATOR: An Educational Laboratory Simulator for DC Power Supply - Khan, Ajmal (2020)
Simulators are excellent illustrative tools that provide facets such as hands on experience of a real world system. Such simulators have enormous efficacy in education where critical thinking and decision making skills can be infused with great effectiveness. These simulators allow students to polish various competencies ranging from application to analysis and from synthesis to evaluation. In this project, a simulator is proposed from the area of electronics. The simulator targets junior to senior level electrical engineering students.